2019
DOI: 10.3390/jcm8091424
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Therapy Modulates Intestinal Microbiota and Reduces Serum Levels of Total and Free Indoxyl Sulfate and P-Cresyl Sulfate in Chronic Kidney Disease (Medika Study)

Abstract: In chronic kidney disease (CKD), the gut-microbiota metabolites indoxyl sulfate (IS) and p-cresyl sulfate (PCS) progressively accumulate due to their high albumin-binding capacity, leading to clinical complications. In a prospective crossover controlled trial, 60 patients with CKD grades 3B–4 (GFR = 21.6 ± 13.2 mL/min) were randomly assigned to two dietary regimens: (i) 3 months of free diet (FD) (FD is the diet usually used by the patient before being enrolled in the Medika study), 6 months of very low protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(109 citation statements)
references
References 57 publications
3
104
2
Order By: Relevance
“…The involvement of Lachnospiraceae species in protein metabolism is less clear. In a previous trial, species of this family showed a marked negative correlation with the protein intake, especially animal proteins (FDR < 0.05) [194]. Additionally, in a study performed using a murine model, the relative abundance of Lachnospiraceae decreased after the consumption of a high-protein/low-carbohydrate diet, compared to a normal diet [204].…”
Section: Diet Modulates Lachnospiraceae Diversitymentioning
confidence: 87%
See 1 more Smart Citation
“…The involvement of Lachnospiraceae species in protein metabolism is less clear. In a previous trial, species of this family showed a marked negative correlation with the protein intake, especially animal proteins (FDR < 0.05) [194]. Additionally, in a study performed using a murine model, the relative abundance of Lachnospiraceae decreased after the consumption of a high-protein/low-carbohydrate diet, compared to a normal diet [204].…”
Section: Diet Modulates Lachnospiraceae Diversitymentioning
confidence: 87%
“…This change at the phylum level was primarily derived from an increased abundance of Blautia and Roseburia [193]. By including data from dietary intake and intestinal OTUs, Di Iorio found that several species of Lachnospiraceae (specifically Blautia wexlerae, B. obeum, B. coccoides, B. hydrogenotrophica, Coprococcus eutactus, Lachnospira pectinoschiza, Pseudobutyrivibrio xylanivorans, and Roseburia faecis) were positively correlated with vegetable proteins, fiber intake, and potassium (FDR < 0.05) [194]. In fact, their ability to use complex plant material and transport degradation products of various sizes and compositions was confirmed by metagenomics studies [21].…”
Section: Diet Modulates Lachnospiraceae Diversitymentioning
confidence: 99%
“…The rationale of this approach is justified by the plastic capacity of gut microbiota to respond to environmental stimuli, primarily nutrition and supplementation [26]. In this regard, our group recently demonstrated that dietary schemes, such as Mediterranean diet and a very low protein diet, are able to modify, in a saccharolytic fashion, gut microbiota in CKD patients and to reduce PCS and IS [41].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the effects of uremic toxins from the intestine. These gut-derived uremic toxins have been shown to play a pivotal role in affecting intestinal homeostasis, as well as inducing inflammation and oxidative stress in the systemic circulation [45,46]. Uremic toxins have been positively associated with NF-κB expression and exhibit positive correlations with CRP levels, iNOS and COX-2 expression [43,47].…”
Section: Oxidative Stress and Ckdmentioning
confidence: 99%
“…Interestingly, although phosphate binders have been widely used for phosphate lowering in CKD patients and are recommended for use in CKD by the Kidney Disease Improving Global Outcomes (KDIGO) guidelines, they have been approved by the Food and Drug Administration (FDA) only for use in ESRD patients [91]. Moreover, nutritional therapy without animal proteins (e.g., when replaced by vegetal proteins, such in as the Very Low Protein Diet; VLPD) can reduce phosphorus levels as well as FGF23 and PTH [46,[92][93][94].…”
Section: Phosphatementioning
confidence: 99%